The Influence of Financial Literacy, Financial Technology and Financial Inclusion on MSME Performance in Bandar Lampung City - Arin Dwi Agustina; Aula Ahmad Hafidh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of financial literacy, financial technology (fintech), and financial inclusion on the performance of micro, small, and medium enterprises (MSMEs) in Bandar Lampung City. Financial literacy is an important factor that allows MSMEs to understand financial products and services effectively. Meanwhile, fintech provides easy access to various financial services, which are expected to improve MSME operations. Financial inclusion, which involves accessibility of financial services for all levels of society, plays an important role in supporting the development of MSMEs.This type of research uses quantitative research with an ex-post-facto approach . The population of this study is MSME actors in Bandar Lampung City with a sample size of 106 MSME actors. The location of the study is in Bandar Lampung City. Data collection was carried out by distributing questionnaires. The validity of the instrument using the Person Product Moment correlation resulted in 53 items being declared valid. The reliability test of the instrument used Alpha Croncah ( α > 0.60), the results showed that all variables were declared reliable. The prerequisites for the analysis were tested through normality, multicollinearity and heteroscedasticity tests. Data analysis using multiple linear regression was used to test the effect of independent variables simultaneously on the dependent variable. The results of the study show that: (1) there is a positive and significant influence of financial literacy on the performance of MSMEs in Bandar Lampung City which is quite large, namely if every 1 unit increase in financial literacy can increase MSME performance by 0.528 units . (2) There is a positive and significant influence of the FinTech variable on the performance of MSMEs in Bandar Lampung City which is quite large, namely if every 1 unit increase in the adoption of financial technology has the potential to increase MSME performance by 0.518 units. (3) There is a positive and significant influence on the financial inclusion variable on the performance of MSMEs in Bandar Lampung City which is smaller, namely an increase of 0.204 units . (4) There is a simultaneous and positive influence of financial literacy, fintech, and financial inclusion on the performance of MSMEs in Bandar Lampung City at a confidence level of 99%.